(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses the evaluation of the results of neuroimaging (magnetic resonance) studies in patients with post-COVID syndrome. Statistical significance of the results was assessed using Student’s test of significance (t) for parametric distribution and Fisher’s test (F) for nonparametric data distribution. Differences were considered significant at 95% confidence interval (P≤0.05).